Report of a Fatal Pediatric Case of Hemophagocytic Lymphohistiocytosis Associated with Pandemic Influenza A (H1N1) Infection in 2009 - Biswas Shrestha; Ahmed Omran; Pengfei Rong; Wei Wang (Pediatrics and Neonatology)
An acute viral infection may lead to death, as seen in the recent novel 2009 influenza A (H1N1) virus pandemic that rapidly spread worldwide. Hemophagocytic lymphohistiocytosis (HLH) is a systemic disorder with high mortality rates and can be triggered by various etiological agents, including viral infections. H1N1-associated HLH is a very rare condition that may cause extremely severe complications leading to multiple organ failure (MOF) and death. We report an unusual case of a rapidly progressive and fatal H1N1 infection that was complicated with HLH and MOF in a previously healthy 8-year-old Asian female who initially presented with fever and abdominal pain. To enable early recognition and proper treatment, physicians should be aware of the possibility of this fatal complication, which may present with unusual initial symptoms.